The Impact of Social Influence, Compatibility and Price on Purchase Intention of Android Android Smartphone - Anam, Choirul; , Prof. Dr. Wahyuddin, M.S (2014)
This research was adopted from previous study conducted in Malaysia. This research study was carried out to explore the influence of social influence, compatibility and price on purchase intention of Android Smartphone. This study had examined the impact of social influence, compatibility and price on purchase intention of Android Smartphone.Questionnaire-based survey was used and 100 sets of questionnaires were distributed to respondents and being analyzed by using SPSS. And multiple regression analysis was used to analyze the data. Descriptive analysis,validity and reliability test, classical assumption test, Pearson correlation analysis, multiple regression analysis and hypothesis test through t and F test, and determination coefficient analysis (R²) were used in quantitative analysis. Data has complied validity, reliability and classical assumption test was processed, so that those are resulting regression equation as follows: